Forecast Uncertainty, Disagreement, and Linear Pools of Density Forecasts - Malte Knüppel; Fabian Krüger (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
In many empirical applications, a combined density forecast is constructed using the linear pool which aggregates several individual density forecasts. We analyze the linear pool in a mean/variance prediction space setup. Our theoretical results indicate that a well-known 'disagreement' term can be detrimental to the linear pool's assessment of forecast uncertainty. We demonstrate this argument in macroeconomic and financial forecasting case studies.
Keywords: C53; 330